2007
DOI: 10.1002/mpr.214
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions and the psychosis phenotype

Abstract: In this paper, we discuss the conceptual background for including a dimensional component to the DSM V diagnoses for psychoses. We review the evidence for a continuous distribution of psychosis like symptoms in the general population and summarise the research validating the clinical usefulness of psychopathological dimensions. We conclude that diagnostic models using both categorical and dimensional representations of psychosis have better predictive validity than either model independently. Dimensions do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 71 publications
5
75
0
1
Order By: Relevance
“…In addition, the results demonstrate a continuous distribution of (hypo)manic symptoms and distress, thus supporting the hypothesis that a dimensional representation may usefully describe the (hypo)manic phenotype (Allardyce et al 2007). Only a small fraction of adolescents and young adults experiencing these phenomena were receiving psychiatric care and the co-occurrence of (hypo)manic episodes with depression was low compared to most of the literature.…”
Section: Resultsmentioning
confidence: 73%
“…In addition, the results demonstrate a continuous distribution of (hypo)manic symptoms and distress, thus supporting the hypothesis that a dimensional representation may usefully describe the (hypo)manic phenotype (Allardyce et al 2007). Only a small fraction of adolescents and young adults experiencing these phenomena were receiving psychiatric care and the co-occurrence of (hypo)manic episodes with depression was low compared to most of the literature.…”
Section: Resultsmentioning
confidence: 73%
“…Considerable overlap in symptom expression is one of the most important arguments that categorical models may not adequately describe psychopathology as it exists in nature (Kendell & Jablensky, 2003). A dimensional model, delineating psychopathology not as a binary phenomenon, but along a continuous scale of severity, may complement the traditional categorical approach (Allardyce et al 2007;Kendler et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…F3) disorders [10,27], other studies found support for a separation of schizoaffective disorders from schizophrenia with regard to clinical picture and outcome [20,28]. A dimensional approach seems to be superior in terms of predictive validity [2], but of course the categorical status of current classification systems, the usefulness and simplicity of categorical decisions [40], and a tendency of human beings to think in categories [13] should not be neglected either. The conclusion is obvious: A combination of the categorical and the dimensional perspective would seem to be the most promising approach.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23,35], and the field of psychotic disorders in particular, e.g. [2,11,39]. Many fruitful methodological approaches have been applied and discussed in this regard in order to identify either categories or dimensions, such as cluster analysis, e.g.…”
Section: Introductionmentioning
confidence: 99%